How does society assess the impact of renewable energy in rural inland areas? Comparative analysis between the province of Jaén (Spain) and Somogy county (Hungary) - Francisco Javier Rodríguez-Segura; Marina Frolova (Investigaciones Geográficas)
This article seeks to contribute to the knowledge of energy transitions in Europe by focusing on community perceptions in two European regions belonging to two divergent spatial models of energy transition on the continent. Through a series of questions, it addresses the social assessment of the impact of renewable energies in three main dimensions: environmental, landscape and socio-economic. The article is based on the comparison of two case studies, the province of Jaén (Spain) and the county of Somogy (Hungary). Both are characterised as rural inland regions with a similar level of renewable energy development (not very high) and fairly similar socio-economic characteristics (agrarian economy and ageing). The results show that there are no major differences between the two territories. In general, there is a tendency to assess the impact of renewable energies as negative, especially in the case of wind farms, with the exception of the positive assessment made by respondents when they were asked about local tourism. However, the option “No impact” was mainly selected by respondents when assessing the impact in most questions. Factors such as the lack of knowledge and information, the lack of social consideration in projects or even a lack of interest towards these topics could explain this social stance.